Knowledge management and M&A networks in China's mature firms. An empirical study - Suleman Bawa; Xie Yongping; Ibn Wahab Benin (Journal of Open Innovation: Technology, Market and Complexity)
This study investigates the influence of knowledge management (KM) and merger and acquisition (M&A) networks on the effectiveness of innovation networks within mature entrepreneurial firms. By focusing on a sample of 4139 firms listed on the Chinese stock market and analyzing 8563 M&A transactions from the mid-2000s to 2023, the research aims to explore how these strategic networks shape entrepreneurial innovation, with particular attention to the moderating role of absorptive capacity (AC) and the impact of entrepreneurial uncertainty. A mixed-method approach, combining structural equation modelling (SEM) and qualitative interviews, was employed to evaluate the relationships between KM, M&A, and innovation networks. SEM facilitated the assessment of hypothesized connections and mediation effects, while interviews with key stakeholders provided qualitative insights into the practical nuances of network interactions and strategies in mature firms. The study finds that KM practices, such as effective planning and knowledge acquisition, alongside M&A networks, collectively enhance the effectiveness of innovation networks. While KM promotes operational and strategic alignment, M&A networks support stakeholder decision-making, thus reinforcing firm operations. Absorptive capacity (AC) significantly mediates the relationship between KM, M&A networks, and innovation network effectiveness. However, entrepreneurial uncertainty diminishes the effectiveness of KM and M&A networks but simultaneously enhances innovation networks' outcomes, underscoring mature firms' adaptability in uncertain environments. This research deepens the understanding of innovation networks in mature entrepreneurial firms by applying the Knowledge-Based View (KBV) framework, highlighting the strategic role of KM and M&A networks. It offers new insights into how mature firms in emerging economies can leverage knowledge assets for sustained innovation and competitive advantage. The findings provide implications for practice and policy, suggesting that mature firms strategically manage KM and M&A activities to enhance innovation networks, even under varying levels of entrepreneurial uncertainty.